Risk factors for haemorrhage in patients with haematological malignancies - Estcourt, LJ (2014)
Haematological malignancies and their treatment lead to prolonged periods of severe thrombocytopenia (platelet count ≤ 50 x 109/l). Despite the use of prophylactic platelet transfusions, haemorrhage remains an important complication during this thrombocytopenic period. Within a 30 day period up to 70% of patients have clinically significant haemorrhage (World Health Organization (WHO) grade 2 or above bleeding) and up to 10% have severe or life-threatening haemorrhage (WHO grade 3 or 4 bleeding). Hence our current management of these patients to prevent haemorrhage is sub-optimal. The aim of this thesis was to identify clinical and laboratory factors that may predict the risk of haemorrhage in patients with haematological malignancies and severe thrombocytopenia. This was achieved via several different study designs and assessed the effect of clinical and laboratory factors on any or clinically significant haemorrhage and their effect on intracranial haemorrhage. This thesis has demonstrated that there is no consensus on how bleeding is assessed and graded in this patient group. Also it showed that the absolute immature platelet number may be a better alternative to the total platelet count to guide administration of platelet transfusions. Female sex, a previous history of a fungal infection, a high C-reactive protein, a high white cell count, a low platelet count, anaemia, impaired renal function, and recent clinically significant haemorrhage were all found to be independent risk factors for haemorrhage. Patients who were in complete remission from their haematological malignancy had a much lower risk of bleeding.